RIPITABILITAS KECEPATAN LARI DAN TINGGI PUNDAK ANAK KUDA PACU UMUR BERBEDA PADA KETURUNAN PEJANTAN â€œMANGUNI MAKASIOWâ€ DENGAN METODE KORELASI DALAM KLAS (Intraclass corelation) - Ambo, Sitty Fatimah S.; Adiani, S.; Paputungan, U; Paat, J. (Universitas Sam Ratulangi, 2014)
SPEED AND BODY HEIGHT REPEATABILITIES OF RACING HORSE AT DIFFERENT AGE IN OFFSPRING FROM â€œMANGUNI MAKASIOUWâ€ MALE PARENT WITH INTRACLASS CORRELATION . This study was conducted to determine the repeatability values of speed and body height at different ages of the offspring from â€œManguni Makasiouwâ€ male parent using intraclass correlation method. Data used in this study were the records of speed to run with various distance of race horse resulting from racehorse competition in North Sulawesi and national PORDASI competition. Running speed data were tabulated using the method of analysis of variance process to obtain the values of repeatabilities. Based on the research and discussion, running speed of racehorse was the highest in the age of five years old and the lowest in the age of two years old. The repeatability values in this study were relatively low, ranging from 0.029-0.047 (running speed) and from 0.029-0.05 (body height). The value of the correlation between running speed and body height at age 2-5 years had high correlation values â€‹â€‹(0.760 to 0.961), indicating that the higher the body height, the higher the level of horse running speed. Keywords: Racing Horses, repeatability, speed, body height, different Ages.